2012
DOI: 10.15560/8.6.1134
|View full text |Cite
|
Sign up to set email alerts
|

Noctuidae moths (Insecta: Lepidoptera) with Iranian type locality

Abstract: A list of 358 noctuid species with Iranian type locality, is proposed belonging to 21 subfamilies. Moreover, the original combination, citation of the original description and synonymy of each species are presented. Xyleninae, Noctuinae and Hadeninae subfamilies constitute the greatest part of the Iranian fauna. The highest numbers of species of these three subfamilies have been recorded from the provinces located in the Zagros and Elburz mountain ranges, by 95 (26.5%), 81 (22.7%) and 46 (12.9%) species, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The Iranian members of Perigrapha are univoltine with early-flying adults that are not commonly caught by the light traps (Shirvani et al, 2012) and the pupa is reported as the overwintering stage. Comparing the genitalia characteristics of P. flora with those illustrated by Hreblay (1996), Shirvani et al (2012) reported this species as new from Iran stating that the more specimens are needed for more accurate decision. Having collected a large number of materials, now we conclude that not only the Iranian fauna includes the P. flora but also comprises the P. cilissa as well.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The Iranian members of Perigrapha are univoltine with early-flying adults that are not commonly caught by the light traps (Shirvani et al, 2012) and the pupa is reported as the overwintering stage. Comparing the genitalia characteristics of P. flora with those illustrated by Hreblay (1996), Shirvani et al (2012) reported this species as new from Iran stating that the more specimens are needed for more accurate decision. Having collected a large number of materials, now we conclude that not only the Iranian fauna includes the P. flora but also comprises the P. cilissa as well.…”
Section: Discussionmentioning
confidence: 79%
“…The genus Perigrapha includes 52 species and 56 subspecies in Eurasia (Volynkin & Matov, 2014) and its members are classified in three subgenera including Opacographa Hreblay, 1996, Rororthosia Beck, 1999, and Perigrapha Lederer, 1857. This genus with five species (Shirvani, 2012;Shirvani et al, 2012) was reviewed in Iran by Shirvani et al (2012). With more than forty species, the members of the Holarctic genus, Egira Duponchel, are classified into five large species groups .…”
Section: Introductionmentioning
confidence: 99%
“…Southeast parts of Iran are biogeographically under the influence of the Oriental region and Kerman fauna shows similarities with eastern countries of Iran (Shirvani, 2012b). For example, Shahreyari-Nejad et al (2020) reported Oncocnemis rhodophaea Ebert, 1978 from Kerman for the first time for Iranian fauna.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse climate Journal of Insect Biodiversity and Systematics 2023  9 (4) conditions in Iran provided a rich faunal assemblage with more than 360 Noctuidae s.l. Species with Iranian-type locality (Shirvani, 2012b;Rajaei et al, 2023a). In the present research, 7 out of 30 recorded species had an Iranian-type locality.…”
Section: Discussionmentioning
confidence: 99%
“…Five Polymixis species of the subgenus Eremophysa, all with Iranian type locality have been described from Iran (Shirvani, 2012b). The present paper describes a new species, Polymixis (Eremophysa) fakherehsabae Shirvani, sp.…”
Section: Introductionmentioning
confidence: 90%